Evaluating probability forecasts in terms of refinement and strictly proper scoring rules - Walter Krämer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
This note gives an easily verified necessary and sufficient condition for one probability forecaster to empirically outperform another one in terms of all strictly proper scoring rules.
Keywords: 519; probability forecasts; scoring rules; refinement